Household food insecurity and hunger status in Debre Berhan town, Central Ethiopia: Community-based cross-sectional study - Demie, Takele Gezahegn; Gessese, Getachew Tilahun (Frontiers in Nutrition, 2023)
Background: Food security occurs when all people have physical, social, and economic access to sufficient, safe, and nutritious food that fits their dietary needs and food preferences for an active and healthy life at all times. There is limited evidence on this topic and not well-studied in Ethiopia Objective: This study aimed to investigate food insecurity and hunger status among households (HHs) in Debre Berhan Town, Ethiopia. Methods: A community-based cross-sectional study was undertaken from January 1 to 30, 2017. A simple random sampling technique was used to enroll 395 HHs for the study. An interviewer-administered structured and pretested questionnaire was used to collect data through a face-to-face interview. The household food security and hunger status were assessed by using Household Food Insecurity Access Scale and Household Hunger Scale respectively. Data were entered and cleaned using Epiata 3.1 and exported to SPSS software version 20 for statistical analysis. Logistic regression was fitted and an odds ratio with a 95% confidence interval (CI) and p-value less than 0.05 was used to identify factors associated with food insecurity. Results: 377 HHs participated in the study with a response rate of 95.4%. The proportion of households with food insecurity was 32.4%, among which mild, moderate, and severe food insecurity accounted for 10.3%, 18.8%, and 3.2% respectively. The mean score of the Household Food Insecurity Access Scale was 1.88 ± 3.5. Hunger occurred among 3.2% of households. The mean Household Hunger Scale score was 2.17 ±1.03. Husband or male cohabitant’s occupation (AOR = 2.68; 95% CI: 1.31-5.48) and wife or female cohabitant literacy (AOR = 3.10; 95% CI: 1.01- 9.55) were the only factors associated with HH food insecurity. Conclusions: HH food insecurity and hunger in Debre Berhan town were unacceptably high which can hamper strive toward national targets for food security, nutrition, and health. Intensified efforts are further needed to accelerate the decline in food insecurity and hunger prevalence. Therefore, interventions need to target self-employed merchants in small businesses and women who are uneducated.